Inclusive Governance and Biodiversity Conservation: Evidence from Sub-Saharan Africa - Ullah, Inayat; Kim, Dong Young (Sustainability, 2021)
We examine the conservation effects attributable to changes in the size of community-governed protected areas (PAs) by adopting a generalized difference-in-difference (DID) design with a two-way fixed effect regression model and synthetic control methods. Panel data from the extraordinary datasets of the World Database on Protected Areas (WDPAs) and the Red List of International Union for the Conservation of Nature (IUCN) are used for 32 Sub-Saharan African countries in this study. Our generalized DID estimates show that countries with community-governed PAs have reduced the IUCN Red List threat level by 17% for mammals. We also find stronger evidence of the effect of community-governed PAs on the IUCN threat level using synthetic control method that allows us to match the “intervention countries” with those countries that exhibit similar pre-intervention threat level. Our results are robust on alternate specifications in which we exploit variations in the cumulative size of the designated PAs differentiated by the IUCN governance types. We also compare the effect of strictly state-governed PAs with community-governed PAs. Our findings provide evidence in support of recent qualitative studies that find positive responses of community participation towards common goods that carry potential economic incentives. This paper contributes to the idea that inclusive environmental policies and legislations yield environmental gains not at the cost of social exclusion.